A Theory of Capital Controls as Dynamic Terms-of-Trade Manipulation - Costinot, Arnaud; Lorenzoni, Guido; Werning, Iván (Journal of Political Economy, 2014)
We develop a theory of capital controls as dynamic terms-of-trade manipulation. We study an infinite-horizon endowment economy with two countries. One country chooses taxes on international capital flows in order to maximize the welfare of its representative agent, while the other country is passive. We show that a country growing faster than the rest of the world has incentives to promote domestic savings by taxing capital inflows or subsidizing capital outflows. Although our theory of capital controls emphasizes interest rate manipulation, the pattern of borrowing and lending, per se, is irrelevant.